Optimization of conditions for topaz irradiation in the WWR-K reactor - Sairanbayev Darkhan S.; Shaimerdenov Asset A.; Aitkulov Magzhan T.; Gizatulin Shamil Kh. (Nukleonika, 2024)
Activation of impurities in topazes happens due to irradiation with thermal neutrons (induced radioactivity occurs), which complicates their further handling. This leads to the need for their long cooling for safe use. The Institute of Nuclear Physics (Kazakhstan) is conducting R&D to develop a method for the effective formation of color centers in topaz during their irradiation in the WWR-K reactor. An irradiation capsule design has been developed in which optimized conditions for irradiating stones in the neutron field of the reactor are formed. The capsule uses shielding materials made of boron carbide and tantalum to cut off thermal neutrons, resulting in a reduction in induced radioactivity in topaz. The effectiveness of the irradiation capsule was tested in the core of the critical facility. As a result, thermal neutron flux is reduced by 5.7 times and the induced activity of the tantalum is reduced by 2.2 times.